1999
DOI: 10.1038/sj.onc.1203104
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of p50-NF-κB and constitutive activation of NF-κB transcription factors during mouse skin carcinogenesis

Abstract: To elucidate the possible role of NF-kB in mouse skin carcinogenesis we studied the expression of p50 (NFkB1), p52 (NF-kB2), p65 (RelA) and IkB-a inhibitor as well as kB-binding activity in adult SENCAR mouse skin, skin papillomas, and squamous cell carcinomas (SCC) generated by a two-stage carcinogenesis protocol. We found that in normal epidermis all of the above proteins were mostly expressed in the cytoplasm of basal cells. Western blot analysis revealed a dramatic increase of p50 and p52 expression in mou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
90
2

Year Published

2000
2000
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(100 citation statements)
references
References 48 publications
8
90
2
Order By: Relevance
“…This could also explain the increased proliferation and enhanced aggressiveness of C57-CYLD C/S cells, as activated nuclear Bcl3/p50/p52 expression has been shown to promote cell proliferation and oncogenesis through the activation of the cyclin D1 gene in breast and nasopharyngeal human tumors (Cogswell et al, 2000;Thornburg et al, 2003). Increased nuclear localization of p50/p52 and Bcl3 was also found in advanced stages of mouse skin carcinomas (Budunova et al, 1999). Nuclear Bcl3 has been detected in cylindroma cells, whereas normal skin keratinocytes retain Bcl3 in the cytoplasm (Massoumi et al, 2006).…”
Section: Discussionmentioning
confidence: 95%
“…This could also explain the increased proliferation and enhanced aggressiveness of C57-CYLD C/S cells, as activated nuclear Bcl3/p50/p52 expression has been shown to promote cell proliferation and oncogenesis through the activation of the cyclin D1 gene in breast and nasopharyngeal human tumors (Cogswell et al, 2000;Thornburg et al, 2003). Increased nuclear localization of p50/p52 and Bcl3 was also found in advanced stages of mouse skin carcinomas (Budunova et al, 1999). Nuclear Bcl3 has been detected in cylindroma cells, whereas normal skin keratinocytes retain Bcl3 in the cytoplasm (Massoumi et al, 2006).…”
Section: Discussionmentioning
confidence: 95%
“…21 BCL-3 also can bind to the promoter of cyclin D1, enhancing progression of the cell cycle from G1 to S phase. 4,22 Several studies have shown that BCL-3 is activated and may play a role in human breast cancer, 23 mouse skin carcinogenesis, 24 and hepatocyte proliferation, 25 which suggest that BCL-3 is involved in carcinogenesis and cell growth. Additionally, it was reported that BCL-3 affects retinoid X receptor functions in some tissues, and that retinoid X receptor plays a role in the potential tumorigenesis mediated by BCL-3.…”
Section: Bcl-3 In Lymphomasmentioning
confidence: 99%
“…Our earlier work revealed that GR overexpression dramatically reduced NF-kB binding activity and expression of kB-responsive genes in skin of K5-GR transgenic mice (Perez et al, 2001). We also showed that NF-kB is constitutively activated in mouse skin tumors induced by the DMBA/TPA protocol, partially because of a strong increase in p50 (NF-kB1) expression and a decrease in the steady-state level of IkBa inhibitor in comparison with untreated epidermis (Budunova et al, 1999). Therefore, we evaluated the NF-kB status in K5-GR/ras+ and w.t./ras+ tumors.…”
Section: Effect Of Gr Overexpression On Nf-kbmentioning
confidence: 99%
“…Whole-cell protein extracts were prepared as previously described (Budunova et al, 1999), separated by SDS-PAGE and transferred to Immobilon-P membrane (Millipore Corporation, Bedford, MA, USA). Membranes were stained with Ponceau S to verify equal protein loading and transfer.…”
Section: Western Blottingmentioning
confidence: 99%